Dukungan Spiritual dan Psikososial Lansia di Panti Sosial Tresna Werdha Kota Bengkulu - Zubaidah Bayan; Yolan Amanda Putri; Cahyani Kaasyifal Ghammi; Egil Olimpia; Gita Permata Sari; Aulia Larasati; Muhammad Fadil Riansyah; Dinda Sucirahmadani (Journal of Society Counseling, 2026)
Psychosocial issues such as loneliness, anxiety, and depression are major challenges for the elderly living in nursing homes due to the loss of family support. This study aims to analyze the role of spiritual support in addressing psychosocial problems among the elderly at the Tresna Werdha Social Home (PSTW) in Bengkulu City. The research method used is qualitative with a phenomenological approach. Data were collected through in-depth interviews, participatory observation, and documentation of informants selected using purposive sampling techniques. Data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data condensation, data display, and conclusion drawing. The results showed that spiritual support, both in the form of communal religious rituals and internal spiritual coping, acts as an emotional anchor that strengthens the resilience of the elderly. This support effectively reduces feelings of isolation and death anxiety by providing a new framework for meaning in life. The conclusion of this study emphasizes that the integration of spiritual support in nursing home management is crucial for maintaining the psychosocial stability of the elderly. It is recommended that the social home develop more personalized and sustainable spiritual guidance programs.